Consideraç\~oes sobre a alocaç\~ao de riscos na concess\~ao do trem de alta velocidade entre Rio de Janeiro, S\~ao Paulo e Campinas - Fabiano Mezadre Pompermayer; Jean Marlo Pepino de Paula (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This work analyses the risk allocation between government and concessionaire in the High Speed Train (HST) Project from Rio de Janeiro to S\~ao Paulo and Campinas. The concession model proposed by the government to transfer the HST operation to private firms in 2010 was revised in 2012, with the main difference between them been on the risk allocation between government and concessionaire related to demand and construction costs. This work assess these two context of HST proposal considering the best practices recommended in the literature, discusses quantitatively how the potential costs of these risks affect the concessionaire's profits and presents some improvements to the current concession model, in an attempt to disseminate good risk allocation practices for infrastructure projects in Brazil.
Keywords: H54; L98; L92; R42; R48; 330; risk allocation; concessions; infrastructure; high speed trains